ANALISIS PAHAM AL-ITTIHAD DAN AL-HULUL DALAM TRADISI TASAWUF ISLAM - Firmansyah Firmansyah (Universitas Islam Malang, 2021)
This research was conducted to find out how the concept of understanding al-ittihad and al-hulul in Islamic Sufism? and how is the influence of al-Ittihad and al-Hulul in the world of Sufism? This research is library research. Primary sources of research come from books on Sufism, mysticism or books relevant to the theme. As for enriching research information, secondary data sources are used from various books and journal articles that are relevant to this research. Research data collection was carried out using documentation techniques. The data analysis used inductive analysis. Based on the data analysis that has been carried out, it can be concluded that the notions of al-ittihad and al-hulul in their development gave a considerable influence on the development of philosophy, such as Al-Suhrawardi in Persia. In Turkey, this understanding contributed greatly to the creation of the Sufi mehfil which was developed by Jalaluddin Rumi. While in Indonesia, this understanding is very obvious in the understanding of manunggaling kawula gusti developed by Shaykh Siti Jenar. In relation to today's materialistic and hedonic human lifestyles, the concept of Sufism described in its understanding and teachings can be a medium to improve the increasingly complex social conditions of human life as a form of repressive action that can be taken.